Clinical significance of head and neck squamous cell cancer biomarkers - Polanska, Hana; Raudenska, Martina; Gumulec, Jaromir; Sztalmachova, Marketa; Adam, Vojtech; Kizek, Rene; Masarik, Michal (Oral oncology, 2014)
Head and neck tumors belong among the six leading causes of cancer death worldwide. The predominant type of head and neck tumors consists of squamous cell carcinomas (HNSCC). Early detection of primary tumor and relapse is a key factor for enhancing the survival rate of HNSCC patients, because high rates of cases are recognized at advanced stages. Accordingly, biomarkers suitable for the early detection of HNSCC are sorely needed to improve patient outcomes. HNSCC evolve through a multistep process by the accumulation of genetic and phenotypic changes. Searching for specific biomarkers capable of characterizing each degree is therefore really essential. In this review, genomic and gene expression alterations of HNSCC are summarized and associated with HPV status, clinicopathological conditions, and patient history from the perspective of potential biomarker utilization. The emphasis is placed on non-invasive markers detectable from saliva and blood and clinically relevant studies are mentioned in particular. These include analyses of tumorous tissues, saliva, and blood from patients with histologically defined tumors; cell culture- and other in vitro-based studies with no clinical correlations are rather excluded.
Keywords: Carcinoma, Squamous Cell; časná detekce nádoru; Tumor markers; Head and neck cancer; Genomics; nádory hlavy a krku; lidé; Cancer; prognóza; Risk Factors; Papillomavirus; Saliva; Head and Neck Neoplasms; nádorové biomarkery; spinocelulární karcinom; miRNA; rizikové faktory; Prognosis; exprese genu; Early Detection of Cancer; Biomarkers, Tumor; Gene Expression; genomika; Humans